Habitual aerobic exercise in healthy postmenopausal women does not augment basal cardiac autonomic activity yet modulates autonomic-metabolic interactions. Issue 6 (25th June 2022) - O'Donnell, Emma; Craig, Jennifer
Abstract: Objective: The aim of the present study was to examine the effects of habitual exercise training and metabolic health on basal cardiac autonomic function and cardiac autonomic recovery after exercise in healthy postmenopausal women (PMW). Methods: Habitually aerobically trained PMW (PMW-tr; 56 ± 1y; n = 11), and untrained PMW (PMW-un; 57 ± 1y; n = 13) and premenopausal women (PreM; ages 26 ± 1y; n = 14) were studied. Cardiac autonomic function, assessed using heart rate variability (HRV), was measured before and one hour after 45-minutes of moderate-intensity exercise (60% VO2peak ). Fast Fourier frequency domain measures of high (HF; 0.15 Hz-0.4 Hz), low (LF; 0.04 Hz-0.15 Hz), very low (VLF; 0.01 Hz-0.04 Hz), and Total (VLF + LF + HF) HRV were assessed. Serum estradiol, insulin, and glucose were determined, and HOMA-IR, an index of insulin resistance, was calculated. Results: In PMW groups, body composition and serum markers did not differ ( P > 0.05). Pre-exercise, heart rate was lower ( P < 0.05) in PMW-tr than PMW-un, yet HRV did not differ ( P > 0.05). In PMW-tr only, HF was inversely associated ( P < 0.05) with insulin ( r = -0.738) and HOMA-IR ( r = -0.758). In PreM, HRV was higher than PMW ( P < 0.05) and was positively correlated with estradiol ( P < 0.05). Postexercise, HRV was decreased within all groups ( P < 0.05) yet remained higher in PreM ( P < 0.05), and similar ( P > 0.05) between PMW. Conclusions: Basal and postexercise HRV does not differ between habitually aerobically trained and untrained PMW. However, greater insulin sensitivity was associated with higher cardiac parasympathetic tone in trained PMW only. Exercise training may favorably modulate cardiac autonomic-metabolic interactions in PMW.